Resilience of zooplankton communities in temperate reservoirs with extreme water level fluctuations. Issue 2 (2nd April 2020) - Murphy, Christina A.; Evans, Allison; Coffin, Brendan; Arismendi, Ivan; Johnson, Sherri L.
ABSTRACT: The importance of zooplankton as a food resource for higher trophic levels, including threatened and endangered salmon species, highlights the need to improve our understanding of the mechanisms that structure reservoir food webs. Pelagic plankton are the dominant primary and secondary producers in reservoirs experiencing extreme water level fluctuations (WLFs). In these systems, we might expect WLFs to promote predictable and homogenized biotic communities. Here we explored whether spring and summer zooplankton communities are homogenized in Pacific Northwest (USA) flood-control reservoirs managed with annual extreme WLFs. In addition, we evaluated whether community resilience is present in a reservoir that has been drained annually since 2011 for salmon passage. We sampled 4 reservoirs during spring and summer, including 1 that was fully drained, resulting in a lotic riverine environment, for 1 week each fall from 2012 to 2016. We found low beta diversity across reservoirs, indicating homogenized communities. Additionally, we did not observe changes across sample years or increased differences in species composition compared to historical data. Instead, we observed strong seasonal transitions that were predictably repeated each year. Our findings support the hypothesis that extreme WLFs, under which these reservoirs have been managed for >50 years, may have structured reservoir zooplankton communities such that they are resilient to even more dramatic draining. Understanding how WLFs and reservoir draining may impact zooplankton will be critical to minimizing unintended consequences of reservoir management on aquatic food webs.